Digital Literacy Practices in Language Pedagogy: Blended Learning/Flipped Classroom on English Language Teaching in Indonesia - Fauris Zuhri; Slamet Setiawan; Syafi'ul Anam (Journal of Languages and Language Teaching)
Digital literacy practices are a current issue and exciting topic, mainly for two reasons: many activities are integrated with digital technology, and one of them is English language teaching, which requires technological innovation to improve English language achievement. This study describes how English language teachers can develop and implement digital literacy practices in English classes. Qualitative research is the methodology utilised in this study, employing online interviews and questionnaires as the research tools. The study results show that many participants want to implement digital literacy practices in English classes. They must make digitally comprehensive preparations, practical implementation, and comprehensive assessments. There are some steps to implement digital literacy practices in English language teaching: adoption, adaptation, application, CALL, and MALL. So, English language teachers should follow five steps to implement digital literacy practices in English classes. The five steps are in line with preparation, implementation, and assessment. Digital literacy practices encourage English language teachers to improve and integrate their English language knowledge, skills, and character day by day. Digital literacy practices help English language teachers develop comprehensive preparation, efficient implementation, and comprehensive assessment more efficiently.